2020
DOI: 10.7710/2162-3309.2349
|View full text |Cite
|
Sign up to set email alerts
|

Stony Brook University Author Perspectives on Article Processing Charges

Abstract: This article underwent semi-anonymous peer review in accordance with JLSC's peer review policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(23 reference statements)
2
2
0
Order By: Relevance
“…Our findings in terms of how authors pay for APCs are consistent with the existing literature, as less than 20% of our respondents reported using personal funds. Similar studies also report the general sentiment that OA journals are of lower quality [12,13], which was reflected in the free text comments left by our faculty respondents. Finally, our results echo the disconnect reported in previous studies, where researchers and authors support the concept of OA but believe that APCs are too expensive and should not be paid by authors.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our findings in terms of how authors pay for APCs are consistent with the existing literature, as less than 20% of our respondents reported using personal funds. Similar studies also report the general sentiment that OA journals are of lower quality [12,13], which was reflected in the free text comments left by our faculty respondents. Finally, our results echo the disconnect reported in previous studies, where researchers and authors support the concept of OA but believe that APCs are too expensive and should not be paid by authors.…”
Section: Discussionsupporting
confidence: 79%
“…Finally, our results echo the disconnect reported in previous studies, where researchers and authors support the concept of OA but believe that APCs are too expensive and should not be paid by authors. Pilato & Tran [13] found that the majority of authors are unwilling to contribute any personal funds to APCs, which reflects our finding that about 70% of respondents Disagree or Strongly Disagree that APCs should be paid by authors. It is clear that despite support for the concept of OA, authors will typically publish behind a paywall when funding is not available.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…As previously mentioned, the academy continues to reward authors who publish in prestigious journals, and that impacts decisions on where faculty choose to publish. Research by Pilato and Tran (2020) carried out at Stony Brook University in the United States (US), found that 83% of respondents prefer to publish in a prestigious journal or a journal of their choice rather than in an open access journal.…”
Section: Literature Reviewmentioning
confidence: 99%